2005
DOI: 10.1203/01.pdr.0000183784.87452.c6
|View full text |Cite
|
Sign up to set email alerts
|

IgA Antibodies, TGF-β1 and -β2, and Soluble CD14 in the Colostrum and Development of Atopy by Age 4

Abstract: Specific defense factors in breast milk together with length of breast-feeding and genetic predisposition may modulate the development of allergy. We studied whether IgA, soluble CD14 (sCD14), or transforming growth factor (TGF)-␤ in colostrum could affect the development of atopy in children up to age 4. From a cohort of 4676, we selected four groups of children with either long or short exclusive breast-feeding (Ͼ3.5 or Ͻ0.5 mo); these groups further differed in the presence or absence of atopic heredity. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
6
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 35 publications
7
104
6
2
Order By: Relevance
“…In partial contrast to our findings, infants with postweaning onset allergic disease received colostrum with higher TGF-␤2 levels than infants with preweaning onset of disease (16). However, this observation is still controversial (15,18,20). That children with transient when compared with persistent sensitization during infancy more often received colostrum with detectable IL-10 may be related to the IgE inhibitory effects of this cytokine (26).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In partial contrast to our findings, infants with postweaning onset allergic disease received colostrum with higher TGF-␤2 levels than infants with preweaning onset of disease (16). However, this observation is still controversial (15,18,20). That children with transient when compared with persistent sensitization during infancy more often received colostrum with detectable IL-10 may be related to the IgE inhibitory effects of this cytokine (26).…”
Section: Discussioncontrasting
confidence: 99%
“…The controversial results regarding the role of breast-feeding for prevention of allergy development have been suggested to be partly because of differences in breast milk composition (12). For instance, high levels of breast milk IgA (13)(14)(15) and TGF-␤ (16,17) have been suggested to affect the allergy development in the child, although this is still controversial (15,18 -20).…”
mentioning
confidence: 99%
“…52 However, in a birth cohort study, concentrations of either TGF-␤1 or TGF-␤2 in colostrum were not associated with the risk of atopic sensitization or allergic disease by the age of 4 years. 26 This discrepancy may be explained by constitutional differences in the risk of developing atopic disease even though atopic heredity was taken into account in subgroup analyses in the latter study.…”
Section: Breastmilk Tgf-␤ and The Development Of Atopic Disease In Thmentioning
confidence: 84%
“…23 Soluble (s)CD14 is found in substantial quantities in breastmilk, 24 and there are epidemiological data suggesting an inverse relationship between breastmilk sCD14 concentrations and the risk of developing atopic disease. 25,26 LeBouder et al 27 have reported that breastmilk modulates innate immune responses to bacterial antigens in human intestinal epithelial cells in vitro. This immunomodulation was demonstrated to be partially dependent on sCD14 in breastmilk.…”
Section: Factors Modulating Intestinal Immunitymentioning
confidence: 99%
“…O CD14 solúvel está presente em altas concentrações no leite materno e tem importante papel na indução da resposta de linfócitos T auxiliares a bactérias, podendo também proteger contra o desenvolvimento de alergias 55 . O alto nível de proteína eosinofílica catiônica também proporciona essa proteção.…”
Section: Doenças Respiratóriasunclassified